Comparative Study of Using Different Educational Technology Types and Their Effect on Learning Free throw In Basketball - Shakir, Zaid (Journal of Physical Education, 2016)
The importance of the research lies in learning free-throw skill using modern educational techniques that makes it easier to learn this skills and lesser to forget. The problem of the research lies in demonstrating the free throw skill and teaching it to the students using repetition of skill in front of the student. The researcher selected (90) first year students of physical education and sport Sciences College / University of Baghdad. The subject were divided equally into three groups; group (a) used film demonstration, group (b) used the traditional explaining and display technique, and group (c) used slideshow presentation of free-throw skill in basketball. The experiment lasted for (8) weeks with (16 hours) range. The researcher concluded that group(a) that used educational film was the best group followed group (b) while group (c) came last.